PEMETAAN KONDISI GEOLOGIS DAN KELERENGAN DAERAH RAWAN LONGSOR DI SESAR SUMATERA WILAYAH KABUPATEN PASAMAN - Muharram, Affan Nurman; Edial, he (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
Pasaman Regency is one of the regencies vulnerable to landslides. This is due to being traversed by the active Sumatra fault line, resulting in tectonic earthquakes. This study aims to determine the geological characteristics, determine the slope level, determine the distribution of rainfall, and produce a landslide-prone area map in the Sumatra fault line area of Pasaman Regency using Geographic Information System (GIS) and Remote Sensing. In this study, the method used is quantitative research with data analysis techniques such as Supervised Classification, Kappa Accuracy Test, Isohyet, and Scoring. The data used include rock types, rock hardness, slope levels, land cover, and rainfall. Overall, Pasaman Regency falls into the moderate category of landslide vulnerability, covering an area of 341.140,17 Ha or 86,58%. This is followed by the high category, covering an area of 51.299,30 Ha or 13,2038%. The smallest category is the low zone with an area of 1.568,99 Ha or 0.40%.